Vitamin D Supplementation Improves Mood in Women with Type 2 Diabetes - Sue Penckofer; Mary Byrn; William Adams; Mary Ann Emanuele; Patricia Mumby; Joanne Kouba; Diane E. Wallis (Journal of Diabetes Research)
Objective. The aim of this study was to determine the effect of vitamin D supplementation on improving mood (depression and anxiety) and health status (mental and physical) in women with type 2 diabetes mellitus (T2DM). Methods. Fifty women with T2DM and significant depressive symptomology were enrolled into the “Sunshine Study,” where weekly vitamin D supplementation (ergocalciferol, 50,000 IU) was given to all participants for six months. The main outcomes included (1) depression (Center for Epidemiologic Studies Depression, CES-D, and Patient Health Questionnaire, PHQ-9), (2) anxiety (State-Trait Anxiety), and (3) health status (Short Form, SF-12). Results. Forty-six women (92%) completed all visits. There was a significant decrease in depression (CES-D and PHQ-9, p<0.001) and anxiety (state and trait, p<0.001). An improvement in mental health status (SF-12, p<0.001) was also found. After controlling for covariates (race, season of enrollment, baseline vitamin D, baseline depression (PHQ-9), and body mass index), the decline in depression remained significant (CES-D, p<0.001). There was a trend for a better response to supplementation for women who were not taking medications for mood (antidepressants or anxiolytics) (p=0.07). Conclusions. Randomized trials to confirm that vitamin D supplementation can improve mood and health status in T2DM women are needed.